"Easy rider" and the conventions of the road movie - Induráin Eraso, Carmen (Huarte de San Juan. Filología y Didáctica de la Lengua, 2000)
This paper concentrates on the basic traits of an archetypal early road movie like Dennis Hopper's "Easy rider". The contrastive analysis of the genre's major influences: the Western and the Beat Generation's philosophy as seen through jack Kerouack's "On the road", together with the study of some influential cultural and historical factors will clarify Easy rider's condition as a male road movie, its harsh criticism on US patriarchal society, its fascination with the depiction of sex and violence but especially, its overwhelming success.